Implementasi Metode Buzz Group dengan Media Lidi sebagai Upaya Meningkatkan Hasil Belajar Matematika Pada Materi Perkalian Bilangan Cacah Kelas II di MI Ma’arif Kaligowong - Siti Endang Lestari; Imam Subarkah; Oky Ristya Trisnawati; Maryanto Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
The purpose of this study was to improve learning outcomes through the applicationof the buzzgroup method with stick media as an effort to improve mathematics learning outcomes on wholenumber material in class II MI Ma'arif Kaligowong. This study uses a Classroom Action Research(CAR) approach with 3 cycles. In this study, the students studied were 29 students of class II MIMa'arif Kaligowong.Data analysis techniques in this study used data reduction, data presentationand data verification. Part of this research uses interview data collection techniques (interviews),questionnaires (questionnaires), observations (observations) and documentation. Whencollecting the data that has been collected then carrying out evaluation actions according to theresearch. The first data collection is the type oftest, where the taking is in the form of mathquestions and shown is the value of mathematics lessons.The data collected is in the form oflearning implementation data using the buzzgroup learning method. The results showed that theapplication of the buzz group method with stick media can improve student learning outcomes,as seen in the increase in math scores. In the initial condition with an average value of 64.79, theaverage value increased in the first cycle to 68.79, in the second cycle the average value increasedto 70.82, and in the third cycle the average value became 73.55